Nucleation of copper nanoparticles on quartz as catalysts to grow single-walled carbon nanotube arrays. (December 2016) - Zhao, Xiulan; Liu, Yu; Cui, Rongli; Li, Yan
Abstract: Horizontally aligned single-walled carbon nanotube (SWNT) arrays are of great importance for building nanoelectronics devices and integrate circuits. We developed a method to grow SWNT arrays uniformly distributed all over the quartz substrate. Instead of pre-patterning catalysts on the substrates, Cu are evaporated under the reductive atmosphere of H2 and nucleate on the surface of quartz to form nanoparticles catalyzing the SWNT growth. Surface roughness is found to take an important role for the nucleation of Cu nanoparticles. We can control the size and density of Cu nanoparticles thus we are able to manipulate the alignment and the density of the grown SWNTs. Because there is no catalyst patterning regions on the substrate, the whole wafer can be used to build electronic devices. This provides great convenience for device fabrication and architecture. Graphical abstract: